Development of a reading test for second language learners of Turkish - Kurt, Yavuz. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
The purpose of this study is to develop a reading test that measures the ability to read in Turkish as a second language. Based on the reading framework by Khalifa and Weir (2009), task specifications were developed and reading tasks with different intended proficiency levels were developed based on the task specifications. The tasks were tested both on native speakers of Turkish and on learners of Turkish from 21 different language backgrounds enrolled in intermediate and advanced level Turkish classes at Boğaziçi University. Test taker data were used to assess item characteristics, reliability and validity of the tasks. Expert judgment was employed to evaluate the reading skills measured by task items. The findings from these investigations provided preliminary evidence for the reliability and validity of the reading tasks under scrutiny.
Keywords: Turkish language -- Reading materials.; Reading -- Examinations -- Study guides.